Noon at Five O'Clock The Short Stories of Arthur Yap - Yap, Arthur (NUS Press, 2014)
This volume marks the recovery and first combined publication of the stories of Arthur Yap (1943-2006). One of Singapore's most important artists, he was an award-winning poet and an accomplished painter. A hitherto neglected facet of Yap's opus, his eight short stories are deceptive in their simplicity, housing within their sparse prose a complex engagement with Singapore society from which he wrote. With his signature minimalistic style, Yap simultaneously perplexes readers with stories of seemingly plotless ambiguity, yet draws them in with familiar characters playing out situations that still resonate in twenty-first century Singapore today. Angus Whitehead's introduction highlights literary nuances in the stories and frames the stories within the wider backdrop of social change of Singapore at the time of Yap's writing. The meticulous critical apparatus make this book of interest to not only the general reader but also students of Singapore and Southeast Asian literature in English.